β-Carboline Alkaloids From the Deep-Sea Fungus Trichoderma sp. MCCC 3A01244 as a New Type of Anti-pulmonary Fibrosis Agent That Inhibits TGF-β/Smad Signaling Pathway - Hao, Meng-Jiao; Chen, Pei-Nan; Li, Hou-Jin; Wu, Feng; Zhang, Guang-Yu; Shao, Zong-Ze; Liu, Xiu-Pian; Ma, Wen-Zhe; Xu, Jun; Mahmud, Taifo; Lan, Wen-Jian (Frontiers in Microbiology, 2022)
COVID-19 causes pulmonary fibrosis, which is a well-known symptom, and effective strategies are still lacking. In the present study, 25 compounds were isolated from the deep-sea fungus Trichoderma sp. MCCC 3A01244. Among them, two β-carboline alkaloids, trichocarbolines A (1) and C (4) are new compounds. The chemical structures of these compounds were elucidated based on their HRESIMS, 1D and 2D NMR spectra, optical rotation calculation, and comparisons with data reported in the literature. Trichocarboline B [(+)- and (–)-enantiomers] had previously been synthesized, and this is its first report as a natural product. Their anti-pulmonary fibrosis (PF) activity and cytotoxicity were investigated. Compounds 1, 11, and 13 strongly inhibited TGF-1-induced total collagen accumulation and showed low cytotoxicity against the HFL1 cell line. Further studies revealed compound 1 inhibited extracellular matrix (ECM) deposition by downregulating the expression of protein fibronectin (FN), proliferating cell nuclear antigen (PCNA), and α-smooth muscle actin (α-SMA). Mechanistic study revealed that compound 1 decreased pulmonary fibrosis by inhibiting the TGF-β/Smad signaling pathway. As a newly identified β-carboline alkaloid, compound 1 may be used as a lead compound for developing more efficient anti-pulmonary fibrosis drugs.